Education and diversity in the context of public schools in Manaus (Research, Society and Development, 2024)
Currently, education within the context of adversity is still a challenge for public schools, in this sense, the general objective of this study is to investigate education and diversity in the context of public schools in Manaus. And its specific objectives are: Analyze the existence or not of policies on diversity in public high schools in Manaus; highlight the practice of LGBTQIA+ inclusion policies within the school context; verify whether teachers received any training on gender identity and sexuality during their academic and professional training period. Methodology, this is field research. The study showed that teachers have difficulty putting LGBTQIA+ inclusion policies into practice within the school context, making it clear from their statements that the educational system in the state of Amazonas lacks training and information on ways to debate issues related to gender identity and sexuality in the school environment, without encountering conflicts, mainly coming from the students' family nucleus. However, even without this necessary support to enable the deepening of themes in the school space, some teachers demonstrate that they work on the issue of gender identity and sexual diversity in some way, thus maintaining the inclusion of students. However, some reported that they did not feel comfortable dealing with these contents, for them these are complicated topics to work on in the classroom, and that they would feel more comfortable if they had training to work on this topic.